Chronic Kidney Diseases and Acute Kidney Injury in Patients With COVID-19: Evidence From a Meta-Analysis - Zhou, Yangzhong; Ren, Qidong; Chen, Gang; Jin, Qiao; Cui, Quexuan; Luo, Huiting; Zheng, Ke; Qin, Yan; Li, Xuemei (Frontiers in Medicine, 2020)
Renal involvement has been implicated in coronavirus disease 2019 (COVID-19), but the related prevalence and prognosis were largely unknown. In this meta-analysis, we searched the literature from PubMed, Embase, through bioRxiv, and medRxiv until April 26, 2020. Studies reporting chronic kidney diseases (CKDs) and/or acute kidney injury (AKI) were included. Demographics, relevant data of disease severity, and patient's prognosis were extracted and aggregated. Twenty-one thousand one hundred sixty-four patients from 52 peer-reviewed studies were included. Thirty-seven studies (n = 16,922) reported CKD in COVID-19 patients at diagnosis, and the pooled prevalence was 3.52% (95% CI, 1.98–5.48%; I2 = 93%). Subgroup analysis showed that CKD prevalence was higher in severe cases [odds ratio (OR), 3.42; 95% CI 2.05–5.61; I2 = 0%] compared to those with non-severe disease and deceased cases (6.46, 3.40–12.29; I2 = 1%) compared with survivors. Pooled prevalence of CKD was lower in Chinese patients (2.56%; 95% CI, 1.79–3.47%; I2 = 80%) compared to those outside of China (6.32%; 95% CI, 0.9–16.12%; I2 = 93%) (p = 0.08). The summary estimates for AKI prevalence was 11.46% (95% CI, 6.93–16.94%). Patients with AKI had a higher prevalence of developing into severe cases (OR, 6.97; 95% CI, 3.53–13.75; I2 = 0%) and mortality risk (45.79, 36.88–56.85; I2 = 17%). The prevalence estimates of CKD or AKI were not significantly different from preprint publications (p > 0.05). Our study indicates that renal condition, either in CKD or AKI, is associated with COVID-19 prognosis, and taking care of such patients needs further awareness and investigations.